2017
DOI: 10.18805/ijare.v51i03.7935
|View full text |Cite
|
Sign up to set email alerts
|

A Study on the performance of Agricultural Sector in India

Abstract: The time series data at all India level on area, production and productivity of foodgrains, production and per capita availability of milk and eggs and production of meat were compiled and a decade wise analysis of growth rate, instability index and decomposition analysis was done to study the performance of agriculture sector. During the overall period, the area under food grains showed negative growth whereas production and productivity growth was positive. For milk and egg, both production and per capita av… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…The economy of India is agriculture based, known for possessing its own rich and diverse knowledge about cultivation practices (Nishant and Upadhyay, 2016). The Indian agricultural sector has undergone tremendous transformation over the years from a state of severe food crisis to self sufficiency in food grain production (Priscilla et al, 2017). Barbados cherry also known as Acerola or West Indian cherry (Malpighia emarginata D.C.) belongs to the member of Malpighiaceae family.…”
mentioning
confidence: 99%
“…The economy of India is agriculture based, known for possessing its own rich and diverse knowledge about cultivation practices (Nishant and Upadhyay, 2016). The Indian agricultural sector has undergone tremendous transformation over the years from a state of severe food crisis to self sufficiency in food grain production (Priscilla et al, 2017). Barbados cherry also known as Acerola or West Indian cherry (Malpighia emarginata D.C.) belongs to the member of Malpighiaceae family.…”
mentioning
confidence: 99%
“…During 1985-86 and 2014-15 the area under food grains has showed negative growth rate in India [compound annual growth rate (CAGR): -0.075] while the productivity growth (CAGR: 1.901) has been positive (Priscilla et al, 2017). Role of new technologies including varieties is imperative under the scenario.…”
Section: Results and Discussion Overall Status Of Varietal Registratimentioning
confidence: 99%
“…This result is also related to [40] alternative raw materials being the primary solution to develop agro products in India. In addition, [41] found that the use of alternative raw materials that are environmentally friendly, especially liquid waste, will improve the performance of the agricultural sector. A broader analysis carried out by [42] was related to the development of alternative raw materials creating forward and backward linkages to agro-industry.…”
Section: Vertical Integration In Gambier Agroindustrymentioning
confidence: 99%